Pre-migration and post-migration factors associated with mental health in humanitarian migrants in Australia and the moderation effect of post-migration stressors: findings from the first wave data of the BNLA cohort study - Renzaho, A; Chen, Wen; Ling, Li; Renzaho, Andre; Hall, Brian (My University, 2017)
Background The process of becoming a humanitarian migrant is potentially damaging to mental health. We examined the association between pre-migration and post-migration potentially traumatic events and stressors and mental health, and assessed the moderating effect of post-migration stressors in humanitarian migrants in Australia. Methods In this study, we used the first wave of data between 2013 and 2014 from the Building a New Life in Australia survey. The survey included 2399 migrants who had arrived in Australia holding a permanent humanitarian visa 3–6 months preceding the survey, with 77% and 23% of participants being granted visas through offshore and onshore humanitarian programmes, respectively. Post-traumatic stress disorder (PTSD) was measured with the Post-traumatic Stress Disorder 8 items (PTSD-8) and severe mental illness was measured with the Kessler Screening Scale for Psychological Distress (K6). Pre-migration potentially traumatic events and post-migration stressors related to asylum process and resettlement were measured with a self-reported questionnaire. Findings Of the 2399 participants, 762 (31%; 95% CI 29·4–33·2) had PTSD and 394 (16%; 95% CI 14·2–17·2) had severe mental illness. The mean number of pre-migration potentially traumatic events was 2·1 (SD 1·4). 64%, 59%, 49%, and 18% of participants reported poor social integration, economic problems, worrying about family or friends overseas, and loneliness as post-migration stressors. Pre-migration potentially traumatic events and post-migration stressors were positively associated with PTSD and severe mental illness. Factors significantly modifying the association between pre-migration potentially traumatic events and mental health after controlling for confounding factors were resettlement related stressors, including loneliness (odds ratio 1·17, 95% CI 1·05–1·28 for PTSD and 1·28, 1·16–1·41 for severe mental illness) and the number of social integration stressors (1·10, 1·05–1·16 for PTSD). Interpretation Our data suggest that post-migration resettlement-related stressors were the most important correlates of mental health in humanitarian migrants, accounting for both direct and indirect associations. Targeting resettlement-related stressors through augmenting psychosocial care programmes and social integration would be a key approach to improve humanitarian migrants' mental health. Funding None.
Keywords: Culture -- Immigrants; Life Events -- Immigration / newly arrived migrants; Health -- Mental; Disadvantage, adversity and resilience; Health and wellbeing; Migration and settlement; Culture; Health; Life Events; Immigration / newly arrived migrants; Immigrants; Mental; Health and wellbeing; Dsiadvantage, adversity and resilience; Migration and settlement; Adversity and resilience